Egyptian fish farmers learn best aquaculture practices - WorldFish (WorldFish, 2014)
Teaching Egyptian fish farmers the industry’s best aquaculture practices has helped increase their production and income. Strengthening the industry’s small and medium-scale farms will generate new employment opportunities and meet the country’s growing demand for fish. The training is part of the Improving Employment and Income through Development of Egypt’s Aquaculture Sector project, which is funded by the Swiss Agency for Development and Cooperation and aims to create 10,000 new industry jobs.